A treatise on wood engravings - historical and practical (1881)... - Internet Archive Book... (Wikimedia Commons, 1881)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Droits : Licence No known copyright restrictions via Wikimedia Commons
Keywords: histoire; iconographie; gravure; photographie; wikimedia commons; Iconographie